2017
DOI: 10.1016/j.jbi.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging health informatics to foster a smart systems response to health disparities and health equity challenges

Abstract: Informaticians are challenged to design health information technology (IT) solutions for complex problems, such as health disparities, but are achieving mixed results in demonstrating a direct impact on health outcomes. This presentation of collective intelligence and the corresponding terms of smart health, knowledge ecosystem, enhanced health disparities informatics capacities, knowledge exchange, big-data, and situational awareness are a means of demonstrating the complex challenges informatics professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…23 These activities can enhance our efforts to model, measure, and manage systems to improve health equity. 24 We found that a targeted informatics-enabled approach to health equity included patient entered demographic data, culturally inclusive standard work, measurement of health disparities, development of community partnerships, outreach to populations with care gaps by teams trained in cultural competency, and progress supported in celebration by the executive leadership.…”
Section: Discussionmentioning
confidence: 96%
“…23 These activities can enhance our efforts to model, measure, and manage systems to improve health equity. 24 We found that a targeted informatics-enabled approach to health equity included patient entered demographic data, culturally inclusive standard work, measurement of health disparities, development of community partnerships, outreach to populations with care gaps by teams trained in cultural competency, and progress supported in celebration by the executive leadership.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, as healthcare moves towards learning healthcare systems (LHS), complexities of race, ancestry, and genetics will likely intensify (Carney and Kong 2017; D’Alessandro, O’Neil, and LaGatta 2017). LHS mark a dissolving boundary between biomedical research and clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Health informatics can enable researchers to detect health disparities that may have otherwise been overlooked, while providing a more comprehensive understanding of the variables contributing to certain health outcomes within marginalized populations 11,12 . Prior work has demonstrated the importance of health informatics research in addressing health equity broadly through assessing complex issues within health care delivery systems, 11 and such research can support opportunities for reducing health disparities and promoting health equity.…”
Section: Health Informatics Researchmentioning
confidence: 99%